Measuring Human Resource Performance with the Human Resource Scorecard Approach: A Study at Balikpapan Baru General Hospital - Azmilla Nurrachmalia Adha; Qurratul Aini (Migration Letters, 2023)
Background: Measuring HRP is an essential factor that can be used to determine the OP. HR is a crucial organizational asset, and its performance can significantly affect customer satisfaction and financial performance, ultimately leading to the organization’s success. Measurement with the HRSC approach can help organizations develop targeted plans to improve their HRP. Method: This is a cross-sectional quantitative study using questionnaires on the Likert scale conducted on nurses and midwives. Validity-reliability tests were performed before data collection. Descriptive analysis was used to process the data, and the CDMG was employed to determine the weight of the KPIs. Results and Discussions: Pearson Correlation resulted in 27 valid statements with a Sig. (2-tailed) value of <0.05, and Cronbach’s Alpha was 0.962. The total number of respondents amounted to 69 people. After conducting CDMG, the KPI result of this hospital is 4.15. The HRSC approach, an HR development strategy, showed good performance results in this study. Conclusions: Although the overall performance from every HRSC perspective is excellent, hospitals must evaluate existing policies or formulate new ones to maintain good performance results.